Potential roles of Garcinia family as antimetabolic syndrome - Asep Kuswandi; Vita Murniati Tarawaan; Hanna Goenawan; Muchtaridi Muchtaridi; Ronny Lesmana (Wolters Kluwer Medknow Publications, 2022)
The incidence rate is directly proportional to the incidence of obesity or overweight and Type 2 diabetes mellitus. Garcinia is a plant that has been proven empirically, preclinically, and clinically to have activities for the avoidance and treatment of metabolic syndrome and on the pathogenesis and pathophysiology caused by the disease. The aim of this study is to create a discussion and summarize information regarding the activity or usefulness of the Garcinia plant. This review article was based on the published journals obtained from Google Scholar, Scopus, and PubMed databases using the keywords Garcinia obesity, Garcinia overweight, and Garcinia metabolic syndrome. Garcinia had many activities related to metabolic syndrome because it was able to reduce body fat mass, blood sugar level, body weight, total cholesterol, and triglyceride level. These activities were mediated by numerous apparatuses of feat together with a reserve of fatty acid synthase, α-amylase, α-glucosidase, and several other enzymes and pathways associated with the metabolic syndrome. Garcinia plant was able to be used as a candidate for a new herbal that had a good effect in treating metabolic syndrome in future.